The ecology of an endemic and rare species with a fragmented distribution: Cyclamen balearlcum Willk in France (ACTA BOTANICA GALLICA, 1996)
The ecology of rare species is largely unknown. Though informations on the ecology of these species, as well as on their biological traits and genetics, are necessary to achieve their conservation. Ecology of Cyclamen balearicum Willk. in France was studied by analysing a set of 40 phyto-ecological releves. This late successional species grows in France under a mediterranean climate, in shaded situations, in sites characterized by moderate to copious precipitations (650 to 1800 mm per year) and frosts occurring each year commonly (mean of the minima of the coldest month from - 0,7 degrees C to + 0,7 degrees C), steep relief and north aspect, stony calcareous soils with blocks, important cover of evergreen woody plants, small number of therophytes, very Low human impact. Quercus ilex L. and Buxus sempervirens L. are very often the dominant tree and shrub species In these sites. Two kinds of habitat were distinguished. They mainly differ on geomorphological features, vegetation height and floristic composition. Ecological patterns were discussed in relation with decisive factors such as shade, frost and drainage, and human impacts. The farm or rarity showed by the species in France was discussed according to the criteria proposed by Rabinowitz. As numerous endemic species with narrow distribution, Cyclamen balearicum Willk. has in France a restricted habitat, but where it grows it is sometimes abundant.

NATURAL GERMINATION AS RESILIENCE COMPONENT IN MEDITERRANEAN COPPICE STANDS OF CASTANEA-SATIVA MILL AND QUERCUS-ILEX L (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1994)
In the Mediterranean basin, most of the present forests derive from original forests where the dominant species was different from the present one. These changes are largely due to human activities reflecting millenia of management and, often, overexploitation. In southern France, for example, palaeoecologists believe that the original malacophyllous deciduous forest of downy oak (Quercus pubescens) was replaced by a sclerophyllous evergreen holm oak (Quercus ilex) coppice in the driest areas, and chestnut (Castanea sativa) orchards or coppices in the `'wettest'' areas. However, for the last several decades, exploitation of these coppice stands has been decreasing. In this study, we addressed the question of the resilience of these managed ecosystems in the fact of changing management schemes, and to determine appropriate strategies and criteria of sustainable development. We present some aspects of the auto-succession after clearcutting of holm oak coppice stands and aspects of the natural regeneration of 4 species (Q. ilex, Q. pubescens, C. sativa, and P. pinaster). The consequences of the contrasted life history strategies are compared to estimate the future of these coppices.

Germination and regeneration mechanisms in Mediterranean degenerate forests (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.